2022
DOI: 10.3389/fcell.2022.873029
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights in the Regulatory Mechanisms of Ferroptosis in Hepatocellular Carcinoma

Abstract: Ferroptosis is a newly defined programmed cell death, which by its mechanism differs from other programmed cell death processes such as apoptosis, necrosis, and autophagy. It has a unique morphology and biological properties that antioxidants and iron-chelating agents can regulate. Ferroptosis has the characteristics of iron ion deposition and dependence on lipid peroxidation. It can affect the progression of many cancers, including liver cancer, by inducing an intracellular iron-dependent accumulation of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 140 publications
(180 reference statements)
0
6
0
Order By: Relevance
“…9 Ferroptosis is regulated by specific pathways, which mainly include iron homeostasis, ROS homeostasis, lipid metabolism, and glutathione metabolism. 10 Previous research has found that fluoride could result in the disordered arrangement of hepatocytes, infiltration of inflammatory cells, lysis or fragmentation of cells, increase in the number of lipid droplets, and mitochondrial damage and reduction. 11 Moreover, fluoride could increase the activities of AST, ALT, ALP, and LDH and elevate the levels of ROS in the liver, 5 which could oxidize unsaturated fatty acids, induce the production of lipid peroxidation, and ultimately damage the structure and function of hepatocytes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Ferroptosis is regulated by specific pathways, which mainly include iron homeostasis, ROS homeostasis, lipid metabolism, and glutathione metabolism. 10 Previous research has found that fluoride could result in the disordered arrangement of hepatocytes, infiltration of inflammatory cells, lysis or fragmentation of cells, increase in the number of lipid droplets, and mitochondrial damage and reduction. 11 Moreover, fluoride could increase the activities of AST, ALT, ALP, and LDH and elevate the levels of ROS in the liver, 5 which could oxidize unsaturated fatty acids, induce the production of lipid peroxidation, and ultimately damage the structure and function of hepatocytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The main ultrastructural features of ferroptosis are smaller mitochondria, increased membrane density, decreased/disappeared cristae density, plasma membrane blebbing, and increased cytoplasmic and lipid peroxidation . Ferroptosis is regulated by specific pathways, which mainly include iron homeostasis, ROS homeostasis, lipid metabolism, and glutathione metabolism . Previous research has found that fluoride could result in the disordered arrangement of hepatocytes, infiltration of inflammatory cells, lysis or fragmentation of cells, increase in the number of lipid droplets, and mitochondrial damage and reduction .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also indicated that FAK may regulate proliferation, survival and angiogenesis of cancer cells, and function as a prognostic indicator of HCC [ 17 ]. In addition, various anti-cancer drugs such as sorafenib may regulate intracellular iron metabolism and lipid peroxidation to promote ferroptosis in HCC cells, which has become a new therapeutic strategy for the treatment of HCC [ 18 , 19 ]. Functional modules of amino acid metabolism included glutathione metabolism, and cysteine and methionine metabolism-related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…For example, combination therapies of chelators or chelators with other anticancer agents could be used in initiating ferroptosis in relation to drug resistance to established therapies. In these cases, the regulation of ferroptosis appears to offer therapeutic solutions for refractory and recurring tumors in almost all types of cancer, metastasis and drug resistance [143][144][145][146][147][148][149][150][151]. In other cases, such as in therapeutic combination with immunotherapy, ferroptosis can be enhanced and improve the efficacy of immunotherapy [152][153][154].…”
Section: Ferroptosis the New Target In Cancer Therapies And The Role ...mentioning
confidence: 99%